FIGURE 4. a–i in Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica) - Soto, Joan J.; Peña, Álvaro L. (Zenodo, 2019)
FIGURE 4. a–i Tubularia longstaffi: a polyp-carrying tube; b male polyp; c blastostyle with developing male gonophores; d blastostyle with fully-grown male gonophores; e female polyp; f blastostyle with fully-grown female gonophores; g–h detail of female gonophores carrying actinulae; i actinulae in different stages of development. j–o Zanclea hicksoni: j early-developing polyp, k expanded young polyps, l expanded polyps with hydrorhizal filaments, m contracted polyp, n–o detail of polyps showing tentacle arrangement in linear clusters (arrows). : Published as part of Soto, Joan J. & Peña, Álvaro L., 2019, Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica), pp. 1-78 in Zootaxa 4570 (1) on page 16, DOI: 10.11646/zootaxa.4570.1.1, http://zenodo.org/record/2608527